Assessment of lung deposition and analysis of the effect of fluticasone/salmeterol hydrofluoroalkane (HFA) pressurized metered dose inhaler (pMDI) in stable persistent asthma patients using functional respiratory imaging. (2nd August 2016) - De Backer, J.; Van Holsbeke, C.; Vos, W.; Vinchurkar, S.; Dorinsky, P.; Rebello, J.; Mangale, M.; Hajian, B.; De Backer, W.
ABSTRACT: Background : Unambiguously for inhaled products, PK measures are best suited for ensuring that the total systemic exposure is equivalent for two products but cannot provide regional information about lung deposition and structural changes. Functional respiratory imaging (FRI) has been demonstrated to be sensitive for distinguishing small but imperative differences related to a single treatment. Methods : In this study FRI is used in 16 asthmatic patients to assess equivalence in regional deposition for two products (fluticasone/salmeterol, test and reference) by directly measuring regional functional and structural changes within the lungs following its administration. Results : No differences were observed between the lung deposition patterns and the effects on lung structure and function of two products, having the same formulation and manufactured by different organizations using FRI. Conclusions : Results using FRI complement PK assessments. The added value of this approach to the conventional clinical methods could be significant.